Landscape Structure and Species Interactions Drive the Distribution of Salmon Carcasses in Coastal Watersheds - Harding, Joel M. S.; Harding, Jennifer N.; Field, Rachel D.; Pendray, Jane E.; Swain, Noel R.; Wagner, Marlene A.; Reynolds, John D. (Frontiers in Ecology and Evolution, 2019)
The disproportionate effects of some species can drive ecosystem processes and shape communities. This study investigates how distributions of spawning Pacific salmon within streams, salmon consumers, and the surrounding landscape mediate the distribution of salmon carcasses to riparian forests and estuaries. This work demonstrates how carcass transfer can vary spatially, within and among watersheds, through differences in pink (Oncorhynchus gorbuscha) and chum (O. keta) salmon distributions within 16 streams on the central coast of British Columbia over a five-year period. Spawning pink salmon concentrated in lower reaches of all streams, whereas chum salmon shifted from lower to upper stream reaches as the area of spawning habitat increased. Salmon carcasses transferred to riparian areas by grey wolves (Canis lupus) were concentrated in estuaries and lower stream reaches; particularly shallow reaches of larger streams surrounded by large meadow expanses. Black and grizzly bears (Ursus americanus and U. arctos) transferred higher numbers and proportions of salmon carcasses to riparian areas compared to wolves, transferred more carcasses in areas of higher spawning density, and tended to focus more on chum salmon. Riparian subsides were increasingly driven by bear-chum salmon associations in upper stream reaches. In addition, lower proportions of salmon carcasses were exported into estuaries when densities of spawning salmon were lower and spawning reaches of streams were longer. This study demonstrates how salmon subsidies vary between and within watersheds as a result of species associations and landscape traits, and provides a nuanced species-specific and spatially explicit understanding of salmon-subsidy dynamics.